The Yin-Yang Military
XII, 248 p. 7 illus., 2 illus. in color.
Keywords: This book examines change processes and the challenge of ambidexterity in military organizations. It discusses how military organizations can better adapt to the complex, and at times chaotic, environments they operate in by developing organizational ambidexterity. The authors identify various multiple tasks and functions of military organizations that require multi-dimensional and often contradictory operational, technological, cultural, and social skills. In analogy to the often-opposed functions performed by the right and left hand of the body, modern military organizations are no longer one-dimensional fighting machines, but characterized by a duality of tasks, such as fighting and peacekeeping which often make part and parcel of one and the same mission. The military is both a “hot” and a “cold” organization (a crisis management organization and a bureaucracy). As such, the book argues that these dualities are not necessarily opposed but can serve as complementary forces, likethe yin and yang, to better the overall performance of these organizations. As a consequence, ambidextrous organizations excel at complex tasking and are adaptable to new challenges. Divided into four parts: 1) structures and networks; 2) cultural issues; 3) tasks and roles; 4) nations and allies, it appeals to scholars of military studies and organization studies as well as professionals working for governmental or military organizations.